Gambaran Sitologi Aspirasi Tiroid pada Diagnosis Curiga Keganasan (Karsinoma Papiler Tiroid) - Rahmiati; Julian Chendrasari; Chairil Hamdani (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2020)
BackgroundThyroid carcinoma is the most common malignancy in the endocrine system. Fine Needle Aspiration Biopsy (FNAB) is a preliminaryexamination to detect thyroid neoplasms. One of FNAB diagnostic category according to Bethesda is Suspicious for Malignancy(SFM). This study was conducted to assess the cytology feature of SFM category and its concordance with histopathologic result.MethodsThis retrospective study is a descriptive categoric study with cross sectional design of 40 samples. Secondary datas were arsip inlaboratory of Anatomical Pathology of FKUI/RSCM collected on 2015 diagnosa as suspect for malignancy of tiroid based onhistopathologic result.ResultsThe histopathological results of SFM were: PTC 20 cases (50%), Hurthle cell carcinoma 2 cases (5%), adenomatous goitre withPTC focus 11 cases (27%), adenomatous goitre with atypical cell 1 case (2%), adenomatous goitre 4 cases (10%), follicularadenoma 1 case (3%), Hashimoto's thyroiditis with atypical cell 1 case (3%). Positive predictive value was 82.5% with 94% ofmalignancies were papillary type. Cytology feature of SFM specimen: cellularity moderate (57.5%), macrofollicular (67.5%), nuclearchange powdery chromatin (85%). Giant cell were 18 cases (45%, cytoplasmic were 20 cases (50%), bubble gum colloid were, 9cases (22.5%).ConclusionMost of SFM specimen have malignant histopathologic result, especially papillary type. The positive predictive value of the SFMcategory is quite high, but there is still disconcordance on histopathologic results.